Crowdsourcing vegetables for farmers’ livelihood improvement: a novel collaborative pilot in Uganda. Resilient seed systems for climate change adaptation and sustainable livelihoods in the East Africa sub-region project progress report - Recha, Tobias; Mubiru, Daudi; Vernooy, Ronnie; Kabakoyo, Elizabeth (2019)
The Alliance of Bioversity and CIAT is implementing a Dutch-supported project entitled: Resilient seed systems for climate change adaptation and sustainable livelihoods in the East Africa sub-region. This work aims to boost timely and affordable access to good-quality seed for a portfolio of crops / varieties for millions of women and men farmers’ and their communities across East Africa. East West Seed (EWS) and the Alliance, in collaboration with the Wageningen Center for Development Innovation, the World Vegetable Centre and National Agricultural Research Organisation (NARO)-Uganda, are combining the EWS farmer training approach and the Alliance’s crowdsourcing methodology in a small pilot initiative on vegetables in Uganda. The targeted portfolio of vegetables include traditional (e.g. green leafy vegetables) and modern ones (e.g. tomato, onion, sweet pepper, cabbage, pumpkin) based on farmers’ interests and marketing opportunities, sourced from EWS, the World Vegetable Centre and farmers’ own gardens. The main objective is to strengthen farmers’ capacity to make better use of crop (vegetable) diversity for multiple livelihood purposes. Based on a situational analysis in the Hoima area, 13 farmers were selected to take part in the pilot. They received training in the various aspects of vegetable management from the EWS Knowledge Transfer team in Uganda. The ultimate aim is scale the pilot to about 1,000 farmers. The main research questions for this initiative are: • What are the promising vegetable varieties that smallholder farmers could integrate in their production system? • How do social and gender variables influence crop/variety selection? • What organizational form can best support the testing and adoption of vegetable new species and varieties?